Visual Dramatization of Political Campaigns on Social Media: Multimodal Analysis of Instagram Accounts of Presidential Candidates in the 2024 General Election - Sandi Dwi Ariadi; Nabilah Ananda Razani; Nanda Adjeng Castity; Via Amalia Lesmana (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The 2024 elections in Indonesia have become a key political contest, with candidates campaigning both in person and through social media, especially Instagram. This study explores the visual dramatization of political campaigns on Instagram by three presidential candidates: Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo. Using a qualitative approach, this study employs Systemic Functional Linguistics (SFL) and multimodal analysis to examine the visual content posted by the candidates. The analysis focuses on how various semiotic resources combine to convey meaning. The findings reveal that Instagram is used by candidates to build their public image, enhance political communication, and employ visual rhetoric to influence voters. This research provides insights into the visual strategies used to shape political messages, aiming to enhance understanding of the role of social media in modern political campaigns.